2017
DOI: 10.1124/jpet.117.243972
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Prevents and Reverses Paclitaxel-Induced Mechanical Allodynia in a Mouse Model of CIPN

Abstract: Chemotherapy-induced peripheral neuropathy (CIPN), a consequence of peripheral nerve fiber dysfunction or degeneration, continues to be a dose-limiting and debilitating side effect during and/or after cancer chemotherapy. Paclitaxel, a taxane commonly used to treat breast, lung, and ovarian cancers, causes CIPN in 59-78% of cancer patients. Novel interventions are needed due to the current lack of effective CIPN treatments. Our studies were designed to investigate whether nicotine can prevent and/or reverse pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 65 publications
5
31
2
1
Order By: Relevance
“…pain (Damaj et al, 1998;Bagdas et al, 2015aKyte et al, 2018). In our current study, nicotine was found to be more potent (27-fold) in alleviating the aversive state than the stretching responses induced by AA injection.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…pain (Damaj et al, 1998;Bagdas et al, 2015aKyte et al, 2018). In our current study, nicotine was found to be more potent (27-fold) in alleviating the aversive state than the stretching responses induced by AA injection.…”
Section: Discussionsupporting
confidence: 58%
“…injection of AA, to compare the potency of nicotine in blocking nociceptive reflex behaviour and place aversion. We have previously demonstrated that nicotine can be antinociceptive in several mouse models of pain (Damaj et al., ; Bagdas et al., , ; Kyte et al., ). In our current study, nicotine was found to be more potent (27‐fold) in alleviating the aversive state than the stretching responses induced by AA injection.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In our recent publication establishing the antinociceptive actions of nicotine in a mouse model of paclitaxel-induced peripheral neuropathy (Kyte et al, 2018), we also reported that nicotine does not stimulate proliferation of nonsmall cell lung cancer (NSCLC) or ovarian cancer cells in vitro, nor enhance NSCLC tumor growth in vivo. This work also demonstrated that nicotine fails to interfere with the antiproliferative and cytotoxic actions of paclitaxel in NSCLC cells in culture, whereas our recent unpublished studies have reproduced these findings in tumor-bearing mice (manuscript in preparation).…”
Section: Introductionmentioning
confidence: 92%
“…In rats, Di Cesare Mannelli et al (2013) demonstrated that acute administration of nicotine can reverse trauma-induced neuropathic pain as well as oxaliplatin-induced cold and mechanical allodynia, both of which are characteristic of chemotherapy-induced peripheral neuropathy (CIPN). Our laboratory, in collaboration with the Damaj group, has also shown that nicotine can both prevent and reverse paclitaxel-induced mechanical allodynia in mice following chronic and acute administration, respectively (Kyte et al, 2018). These two reports are, to our knowledge, currently the only publications investigating the use of nicotine in CIPN animal models, indicating that there is a need to explore the antiallodynic property of nicotine with other classes of cancer chemotherapy drugs that cause CIPN, such as the vinca alkaloids and bortezomib.…”
Section: Introductionmentioning
confidence: 96%